Ações municipais para oferta de alimentação escolar durante a pandemia da covid 19 no ano de 2020: um retrato da região imediata de Abaetetuba/Pa. - CAMPOS, Jenifer Lopes (2023)
School meals are a right guaranteed in the Federal Constitution of Brazil, and it is the State's duty to guarantee all students enrolled in the public basic education system. Since March 2020, with the declaration of the pandemic by COVID19, several measures have been taken to control the disease, including the suspension of inperson classes, putting at risk the guarantee of the human right to school meals in the public education system. In view of this, this study aimed to describe the municipal actions implemented in the intermediate region of Abaetetuba to ensure school feeding during the period of the sanitary crisis at COVID 19. This is a cross sectional, quantitative study. The information was obtained through a database, where it was standardized, cleared of duplicates and statistics were performed using Excel and Epi Info 7 software. The results showed that the executing entities of the municipalities in the immediate region of Abaetetuba carried out actions to distribution and distribution of food purchased with PNAE resources. While important, these strategies are limited in scope. In this period of sanitary crisis at COVID 19 and due to the increase in social vulnerability, the PNAE assumes a fundamental role in fighting hunger. Therefore, government officials must preserve and expand the actions of the PNAE.